Pengaruh Gaya Hidup, Label Halal dan Harga terhadap Keputusan Pembelian Kosmetik (Studi Kasus pada Produk Safi) - Ayif Fathurrahman; Martyas Anggesti (Universitas Islam Lamongan, 2021)
Abstract: Style development changes every year. Indonesia, where the population majority is Muslim, is now developing an Islamic lifestyle. This style development can be supported by the inclusion of halal labeling on product packaging. The halal label on the product guarantees that the product is safe for consumption or use. Muslim consumers will consider this before making a purchase indeed. Safi product is a cosmetic product that is halal and safe because they do not contain harmful ingredients. This study aims to analyze the purchasing decision of students for Safi Cosmetics at Universitas Muhammadiyah Yogyakarta and what factors influence the purchasing decision for Safi Cosmetics. This study used data from 120 people. The sample collection used the purposive sampling technique and multiple regression analysis in analyzing primary data. The analytical tool used in this study is the SPSS version 21.0 for windows software. The results obtained in this study are lifestyle variables, halal labels, and prices have a positive and significant effect on students' purchasing decisions for Safi Cosmetic at Universitas Muhammadiyah Yogyakarta. This study shows that the coefficient of determination is 0.484 or 48.4%. The decision of students at the Universitas Muhammadiyah Yogyakarta to purchase Safi Cosmetics can be shown that 48.4% is influenced by lifestyle, halal labels, and prices. Meanwhile, 51.6% is explained by other variables outside the model.